RELASI GENDER PADA MASYARAKAT ADAT LAMPUNG PAGAR DEWA - Asyrofi, Imam; Githo, Githo; Iswanto, Iswanto; azhar, immawan (Kafa`ah: Journal of Gender Studies, 2023)
The indigenous people of Lampung Pagar Dewa Tulang Bawang Barat distinguish between men and women, men in the public domain, and women in the domestic sphere. The gender distinction in the "Pepadun" society is none other than the patriarchal system that has been cultivated and its impact on indigenous women. This study aims to analyze patriarchal gender relations and their impact on women in the indigenous people of Lampung Pagar Dewa Tulang Bawang Barat. This research uses a qualitative descriptive method with a case study approach in the indigenous people of Lampung Pagar Dewa Tulang Bawang Barat. Research data is primary data which is directly obtained from the results of field observations then in-depth interviews and Focus Group Discussions (FGD), secondary data is also obtained from various sources according to the research topic. Data was analyzed by qualitative descriptive method. The results showed that traditionally "Pepadun" society views the social status of men as having to be higher than that of women and the position of women should be subordinated to men. This is evidenced through the marriage system and the applied inheritance system. Indigenous-based patriarchal cultures create injustice for Indigenous women. The division of roles forms a functional social structure that is supposed to protect women but there are dysfunctional men. The dominance of patriarchy is increasingly excessive, causing gender injustice which boils down to cases of violence against indigenous women in Lampung Pagar Dewa Tulang Bawang Barat